Causal relationship between gut microflora and dementia: a Mendelian randomization study - Fu, Jinjie; Qin, Yuan; Xiao, Lingyong; Dai, Xiaoyu (Frontiers in Microbiology, 2024)
Background Numerous pertinent investigations have demonstrated a correlation between gut microflora (GM) and the occurrence of dementia. However, a causal connection between GM and dementia and its subtypes has not yet been clarified. Objective To explore the causal association between GM and dementia, including its subtypes, a two-sample Mendelian randomization (TSMR) analysis was used. Methods Our data comes from the Genome-Wide Association Study (GWAS). The principal approach employed for the Mendelian randomization study was the inverse-variance weighted method, supplemented by four methods: MR-Egger, weighted median, simple mode, and weighted mode. This was followed by Cochrane’s Q test, MR-Egger intercept test, MR-PRESSO global test, and leave-one-out as sensitivity analysis validation. Results Twenty-one GMs associated with any dementia, Alzheimer’s disease, vascular dementia, Lewy body dementia, Parkinson’s disease, and dementia under other disease classifications were derived from the analysis, and 21 passed sensitivity tests. Conclusion We confirmed the causal relationship between GM and dementia and its subtypes, derived specific flora associated with increased or decreased risk of dementia, and provided new ideas for preventive, diagnostic, and therapeutic interventions for dementia mediated by gut microbiota.